Optimal siting of onshore wind turbines: Local disamenities matter - Paul Lehmann; Felix Reutter; Philip Tafarte (Helmholtz-Zentrum für Umweltforschung (UFZ), 2021)
The deployment of onshore wind power is an important means to mitigate climate change. However, wind turbines also produce local disamenities to residents living next to them, mainly due to noise emissions and visual effects. Our paper analyzes how the presence of local disamenities affects the socially optimal siting of onshore wind power. The analysis builds on a spatial optimization model using geographical information system (GIS) data for Germany. Our results indicate a major spatial trade-off between the goals of minimizing electricity generation and disamenity costs. Considering disamenity costs substantially alters - and in fact dominates - the socially optimal spatial allocation of wind power deployment. This is because in Germany a) the spatial correlation between generation costs and disamenity costs is only moderately positive, and b) disamenity costs exhibit a larger spatial heterogeneity than the generation costs. These results are robust to variations in the level and slope of the disamenity cost function that we assume for the modeling. Our findings emphasize the importance of supplementing support schemes for wind power deployment with approaches that address local disamenties, e.g., compensation payments to local residents or minimum settlement distances.
Keywords: D62; Q42; Q51; Q53; R14; 330; Externality; Germany; renewable energy; spatial optimization; wind power